PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK KVISOFT PADA MATERI BAGIAN TUMBUHAN DAN FUNGSINYA DI KELAS IV SDN 004 SAMARINDA ULU - Gresia Kristinawati; Muhlis; Rosita Putri Rahmi; Khusnul Khotimah; Yana Supriyatna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of the Flipbook Kvisoft media aims to enhance the effectiveness of science learning, specifically on the topic of plant parts and their functions, for fourth-grade students at SDN 004 Samarinda Ulu. This media is designed to be interactive, engaging, and support both students’ and teachers’ needs, thereby increasing motivation, understanding, and reducing boredom in the learning process. This study employed a Research and Development (R&D) method using the 4D development model (Define, Design, Development, and Dissemination). The research development procedure also followed the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of the research and discussion on the development of the Flipbook Kvisoft media for science learning on plant parts and their functions in fourth-grade students at SDN 004 Samarinda Ulu were declared "Highly Feasible" for use in the learning process. Based on the feasibility test results, media validation by media experts obtained a percentage of 84% in the "Highly Feasible" category, while material validation by content experts obtained a percentage of 92% in the "Highly Feasible" category. Meanwhile, the student response questionnaire obtained a percentage of 91% in the "Excellent" category. Therefore, the use of Flipbook Kvisoft media in science learning on plant parts and their functions in fourth-grade students at SDN 004 Samarinda Ulu can be concluded as highly feasible and can be used in the learning process to produce interesting and interactive learning.